A gestao do evento Xterra Camp Paraná : Análise do seu impacto na perspectiva dos participantes - Bavaresco, Gustavo (Educación Física y Ciencia.)
The study intends to be a contribution to the managers of sporting events, from the perspective of the participants in the event XTerra Camp Paraná that took place outside the large Brazilian urban centers. This is a quantitative descriptive study, in which a questionnaire was used, reviewed by specialists such as university professors and managers. The main results show (i) a profile of male and non-resident majority participants; (ii) expenses ranged between 100 and 500 reais; and (iii) high satisfaction with the course, organization of the event and region. It is concluded that, from the perspective of the participants, they were globally satisfied with the event because of its efficient organization and the tourist activities associated to it.